2016
DOI: 10.1021/acs.bioconjchem.5b00525
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Experimental Melioidosis with a Synthetic manno-Heptopyranose Hexasaccharide Glycoconjugate

Abstract: Melioidosis is an emerging infectious disease caused by Burkholderia pseudomallei and is associated with high morbidity and mortality rates in endemic areas. Antibiotic treatment is protracted and not always successful; even with appropriate therapy, up to 40% of individuals presenting with melioidosis in Thailand succumb to infection. In these circumstances, an effective vaccine has the potential to have a dramatic impact on both the scale and the severity of disease. Currently, no vaccines are licensed for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 67 publications
1
40
0
Order By: Relevance
“…Indeed, a hexamer conjugated to protein is sufficient to confer protection in a mouse model. 28 Dillon et al. demonstrate that an IgG3 anti-CPS antibody (3C5; composed of Vh6 and IgKV19/28 chains) raised against heat killed B. pseudomallei has a strong affinity for purified CPS.…”
mentioning
confidence: 99%
“…Indeed, a hexamer conjugated to protein is sufficient to confer protection in a mouse model. 28 Dillon et al. demonstrate that an IgG3 anti-CPS antibody (3C5; composed of Vh6 and IgKV19/28 chains) raised against heat killed B. pseudomallei has a strong affinity for purified CPS.…”
mentioning
confidence: 99%
“…In another study, intraperitoneal immunization with chemically synthesized CPS conjugated to tetanus toxoid promoted IgM and IgG serum antibodies. While the CPS-specific antibody titres were considerably less than that induced by native CPS, BALB/c mice were still significantly protected from B. pseudomallei challenge, with 66% of mice surviving until the study end-point at day 35 [47]. In addition to CPS-based conjugates, immunization with the B. pseudomallei O-polysaccharide (OPS II) conjugated to a carrier protein AcrA from Campylobacter jejuni provided similar levels of protection to immunization with whole-cell killed bacteria against a highly lethal challenge [48].…”
Section: Multi-component Vaccinesmentioning
confidence: 91%
“…Importantly, B. pseudomallei appears to express only a single capsule serotype, suggesting that a CPS-based vaccine could confer protection against all B. pseudomallei strains. While the CPS-specific antibody titres were considerably less than that induced by native CPS, BALB/c mice were still significantly protected from B. pseudomallei challenge, with 66% of mice surviving until the study end-point at day 35 [47]. In a recent study, B. pseudomallei CPS was purified and covalently linked to recombinant CRM197, a non-toxic mutant of diphtheria toxin.…”
Section: Multi-component Vaccinesmentioning
confidence: 99%
“…Another strategy has been to produce polysaccharides synthetically in blocks. The exact number can vary, such as a di-and tetra-saccharides (Budhadev & Mukhopadhyay, 2015), di-and tri-saccharides (Mandal, 2014;Mondal, Liao, Mondal, & Guo, 2015;Si & Misra, 2016), three disaccharides (Scott et al, 2016) and two tri-saccharides (Seeberger, Pereira, & Govindan, 2017). However, it should be noted that it is possible to compare assembly methods and one study revealed that linear assembly may be more effective than block assembly (Dhara & Misra, 2015;Seeberger et al, 2017).…”
Section: Polysaccharide Productionmentioning
confidence: 99%